2021
DOI: 10.1007/s10936-020-09752-1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Students’ Use of Zoom Application in Language Course Based on the Technology Acceptance Model (TAM)

Abstract: The study uses technology acceptance model (TAM) to gain insights into user reactions to the technology adopted for language learning. The study aims to analyze the correlation between the variables of TAM on using Zoom application in language learning, in addition to examining how gender and experience influence the use of technology. The participants of this study comprise of 75 undergraduate English-as-Foreign-Language learners who have studied for their courses online during the COVID-19 pandemic. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
136
2
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(224 citation statements)
references
References 54 publications
11
136
2
11
Order By: Relevance
“…In accordance with the above, it is evident that there are more researchers who have used Subjective Norm, for example [59], [78], [82], [83], [1], [26], [85], [86], [87], [88], [89], [90], [91], [92], Experience in the internet & computer [59], [77], [81], [82], [84], [85], [93], [94], [95], [96], [97] Self-Efficacy [59], [83], [84], [85], [1], [71], [72], [73], [86], [95], [98], [99], [74], [97], Technical Support [59], [42], [73], [74], [83], [100], [101], [102] and Anxiety [72], [73],…”
Section: External Variables Of Tammentioning
confidence: 99%
See 3 more Smart Citations
“…In accordance with the above, it is evident that there are more researchers who have used Subjective Norm, for example [59], [78], [82], [83], [1], [26], [85], [86], [87], [88], [89], [90], [91], [92], Experience in the internet & computer [59], [77], [81], [82], [84], [85], [93], [94], [95], [96], [97] Self-Efficacy [59], [83], [84], [85], [1], [71], [72], [73], [86], [95], [98], [99], [74], [97], Technical Support [59], [42], [73], [74], [83], [100], [101], [102] and Anxiety [72], [73],…”
Section: External Variables Of Tammentioning
confidence: 99%
“…Researchers [96], [97], [122] emphasized that Experience in the internet and Computer has no significant impact on Perceived Usefulness while other researchers [59], [76], [82], [94], [95], [123] identified that Experience in the internet and computer has a significantly impact on Perceived Usefulness further confirmed that Experience in the internet and Computer has a significant positive impact on the Perceived Usefulness [76], [82], [94], [95], [123] while researcher [59] found that Experience in the internet and Computer has a significant negative impact on the Perceived Usefulness.…”
Section: Experience In the Internet And Computermentioning
confidence: 99%
See 2 more Smart Citations
“…In this vein, TRI measured people's tendency to accept and utilise modern technologies [39]. The four TRI dimensions are listed as follows [39,40] Although the original TAM was established in 1989 and TRI was established in 2000, both theories are still valid and recently there are still numerous researchers are using TAM and TRI models to measure the user acceptance and readiness of new emerging technologies on various applications such as acceptance of Airbnb sharing accommodation [64], online learning system [65], facial recognition payment [66], e-learning adoption [67], students' use of Zoom application [68], online food delivering ordering services [69], adoption of self-service technology [70] and virtual reality in fashion retailing [71].…”
Section: The Trimentioning
confidence: 99%